Size controlled iron oxide nano octahedra obtained via sonochemistry and natural ageing - Mandel, Karl; Kolb, C.; Strasser, M.; Dembski, S.; Sextl, G. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
Iron oxide nano octahedra were synthesized from iron sulfate in a facile, fast and inexpensive way. Exposure to ultrasound during precipitation of the iron salt with sodium hydroxide in combination with addition of nitric acid was found to predetermine the shape of the particles, which grow in a subsequent natural ageing process. Simply by controlling the ageing time, the size of well-defined iron oxide nano octahedra can be controlled in the range from 80 to 120. nm, which ultimately influences the magnetic properties of the particles. © 2014 Elsevier B.V.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Iron oxide nanoparticles; Octahedra; Shape control; Size control; Ultrasound